Physical Properties of Thin PVDF/MWNT (Multi-Walled Carbon Nanotube) Composite Films by Melt Blending - Hong, Soon Man; Hwang, Seung Sang (AMER SCIENTIFIC PUBLISHERS, 2008)
Poly(vinylidene fluoride)(PVDF)/Multi-walled carbon nanotube (MWNT) composites were melt blended using internal mixer. The relationships between structures and physical properties of thin PVDF/MWNT composite films were studied. With increasing the content of MWNT the size of spherulites in PVDF decreased. MWNT was used as a nucleating agent. The incorporation of MWNT produced a polar beta-form crystal structure of PVDF The permittivities of thin PVDF/MWNT composite films were increased with increasing the MWNT content. The percolation level in electrical conductivity occurred between 2 and 2.5 wt%. The critical conductivity saturation point for the electrical conductivity in PVDF was confirmed. Similar tendency was also observed in thermal conductivity.
Keywords: CRYSTALLIZATION; FIBERS